Observations of collimated ionization channels in aluminum-coated glass targets irradiated by ultraintense laser pulses - Borghesi, M; Mackinnon, A; Bell, A; Malka, G; Vickers, C; Willi, O; Davies, JR; Pukhov, A; Meyer-ter-Vehn, J (1999)
Filamentary ionization tracks have been observed via optical probing inside Al-coated glass targets after the interaction of a picosecond 20-TW laser pulse at intensities above 10 19 W/cm 2. The tracks, up to 700 μm in length and between 10 and 20 μm in width, originate from the focal spot region of the laser beam. Simulations performed with 3D particle-in-cell and 2D Fokker-Planck hybrid codes indicate that the observations are consistent with ionization induced in the glass target by magnetized, collimated beams of high-energy electrons produced during the laser interaction.